Peer Learning As One of the Pathways to Educational Equity - Małgorzata Sławińska (Jan Dlugosz University, 2023)
This article discusses peer learning as a strategy that promotes equity in institutionalized education. Peer learning is a process where students learn from their peers during formal and informal interactions without significant intervention from the teacher. Three types of peer learning were discussed: peer tutoring, cooperative learning, and collaborative learning. The key elements of each type of peer learning were identified, and their role in equalizing educational opportunities was analyzed. In this context, peer learning promotes student participation and engagement, and it improves the academic performance of all students in a diverse classroom.